Optimization of Culture Conditions for Stem Cells Derived from Human Anterior Cruciate Ligament and Bone Marrow. Issue 7 (July 2014) - Cheng, Ming-Te; Liu, Chien-Lin; Chen, Tain-Hsiung; Lee, Oscar K.
Tissue engineering with stem cells is a fascinating approach for treating anterior cruciate ligament (ACL) injuries. In our previous study, stem cells isolated from the human anterior cruciate ligament were shown to possess extensive proliferation and differentiation capabilities when treated with specific growth factors. However, optimal culture conditions and the usefulness of fetal bovine serum (FBS) as a growth factor in in vitro culture systems are yet to be determined. In this study, we compared the effects of different culture media containing combinations of various concentrations of FBS and the growth factors basic fibroblastic growth factor (bFGF) and transforming growth factor-β1 (TGF-β1) on the proliferation and differentiation of ligament-derived stem cells (LSCs) and bone marrow mesenchymal stem cells (BMSCs). We found that α-MEM plus 10% FBS and bFGF was able to maintain both LSCs and BMSCs in a relatively undifferentiated state but with lower major extracellular matrix (ECM) component gene expression and protein production, which is beneficial for stem cell expansion. However, the differentiation and proliferation potentials of LSCs and BMSCs were increased when cultured in MesenPRO, a commercially available stem cell medium containing 2% FBS. MesenPRO in conjunction with TGF-β1 had the greatest ability to induce the differentiation of BMSCs and LSCs to ligament fibroblasts, which was evidenced by the highest ligamentous ECM gene expression and protein production. These results indicate that culture media and growth factors play a very important role in the success of tissue engineering. With α-MEM plus 10% FBS and bFGF, rapid proliferation of stem cells can be achieved. In this study, MesenPRO was able to promote differentiation of both LSCs and BMSCs to ligament fibroblasts. Differentiation was further increased by TGF-β1. With increasing understanding of the effects of different culture media and growth factors, manipulation of stem cells in the desired direction for ligament tissue engineering can be achieved.